From circular consumers to carriers of (unsustainable) practices: socio-spatial transformations in the Circular City. Issue 6 (2nd July 2020) - Hobson, Kersty
ABSTRACT: Debates about the 'Circular City' have underscored the need to rethink consumption practices within urban spaces. This intervention explores these arguments, and suggests that some research and interventions to date have under-played the relationship between unsustainable consumption practices and urban spatial forms, drawing on work into mobile phones and the 'circular consumer'.